2023
DOI: 10.1029/2023ja031419
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Cusp‐Aligned Arcs With Plasma in the Magnetotail Implies a Closed Magnetosphere

Abstract: We investigate a 15‐day period in October 2011. Auroral observations by the Special Sensor Ultraviolet Spectrographic Imager instrument onboard the Defense Meteorological Satellite Program F16, F17, and F18 spacecraft indicate that the polar regions were covered by weak cusp‐aligned arc (CAA) emissions whenever the interplanetary magnetic field (IMF) clock angle was small, |θ| < 45°, which amounted to 30% of the time. Simultaneous observations of ions and electrons in the tail by the Cluster C4 and Geotail spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(28 citation statements)
references
References 80 publications
(196 reference statements)
13
15
0
Order By: Relevance
“…These observations of the more distant magnetotail support the interpretation of Milan et al (2023) that the plasma is trapped on closed magnetic field lines during periods where the magnetosphere is almost-entirely closed as a result of dual-lobe reconnection occurring under northward IMF conditions. Milan et al (2023) suggested that the trapped plasma population in the magnetotail observed by Cluster and Geotail could be the source plasma for cusp-aligned arc (CAA) signatures that were observed simultaneously in the polar region in their study. The CAA emission has been found to have inverted-V precipitation signatures suggesting that the plasma is accelerated down into the polar cap by field-aligned currents associated with flow shears in the convection pattern (Q.-H. Zhang et al, 2020;Milan et al, 2022).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…These observations of the more distant magnetotail support the interpretation of Milan et al (2023) that the plasma is trapped on closed magnetic field lines during periods where the magnetosphere is almost-entirely closed as a result of dual-lobe reconnection occurring under northward IMF conditions. Milan et al (2023) suggested that the trapped plasma population in the magnetotail observed by Cluster and Geotail could be the source plasma for cusp-aligned arc (CAA) signatures that were observed simultaneously in the polar region in their study. The CAA emission has been found to have inverted-V precipitation signatures suggesting that the plasma is accelerated down into the polar cap by field-aligned currents associated with flow shears in the convection pattern (Q.-H. Zhang et al, 2020;Milan et al, 2022).…”
Section: Discussionsupporting
confidence: 78%
“…The plasma in the magnetotail is coincident with simultaneous observations of similar plasma signatures observed in Cluster and Geotail data during the same period investigated by Milan et al (2023). Using pitch angle data available from the CIS and PEACE instruments onboard Cluster, Milan et al (2023) showed that the observed ion fluxes had pitch angles of 0°and 180°indicating two counter streaming ion populations whereas the electron population showed a double loss-cone distribution. Both of these pitch angle distributions indicate that the plasma is trapped on closed field lines.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations